Measurement of nonbillable service value activities by nurse practitioners, physician assistants, and clinical nurse specialists in ambulatory specialty care. Issue 3 (30th March 2021) - Winter, Shira; Chan, Garrett K.; Kuriakose, Clair; Duderstadt, Karen; Spetz, Joanne; Hsieh, Debbie; Platon, Charlene; Chapman, Susan A.
ABSTRACT: Background: Revenue-generating health care activities, generally accepted as a measure of productivity, do not account for the full range of health care activities that enhance patient care. Purpose: We analyzed the quantity, duration, and type of "service value activities" performed by nurse practitioners (NPs), physician assistants (PAs), and clinical nurse specialists (CNSs), which are nonbillable service activities that contribute to billable service provision, quality of care, and value of care. Methods: Data were obtained from ambulatory specialties at one health care institution over a 13-month period. First, descriptive statistics were calculated by time-based code for each category of provider (medical, surgical, transplant, hematology/oncology, and anesthesia). Then qualitative comments were analyzed for frequency of key words. Results: Each provider spent an estimated average of between 3.7 and 36.5 hours per month on service value activities, with the greatest number of these activities related to orders, chart review, and documentation. Implications for practice: More thorough exploration of the quantity and type of service value activities performed may lead to a better understanding of the role and contribution of NPs, PAs, CNSs, and other health care professionals to patient care.